2018
DOI: 10.1002/adhm.201800347
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Applications of Prussian Blue Nanoparticles in Biomedicine

Abstract: Prussian blue nanoparticles (PBNPs) with favorable biocompatibility and unique properties have captured the attention of extensive biomedical researchers. A great progress is made in the application of PBNPs as therapy and diagnostics agents in biomedicine. This review begins with the recent synthetic strategies of PBNPs and the regulatory approaches for their size, shape, and uniformity. Then, according to the different properties of PBNPs, their application in biomedicine is summarized in detail. With modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
167
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 134 publications
0
167
0
1
Order By: Relevance
“…The C‐HSA‐BOPx‐IR825 NP was employed to test the pH in the tumor region by both ratiometric PA and fluorescence imaging. Other NIR dyes, including naphthalocyanines, phthalocyanine, croconine, squaraine, and Prussian blue, can also serve as PA contrast agents.…”
Section: Organic Contrast Agentsmentioning
confidence: 99%
“…The C‐HSA‐BOPx‐IR825 NP was employed to test the pH in the tumor region by both ratiometric PA and fluorescence imaging. Other NIR dyes, including naphthalocyanines, phthalocyanine, croconine, squaraine, and Prussian blue, can also serve as PA contrast agents.…”
Section: Organic Contrast Agentsmentioning
confidence: 99%
“…1A) showed multiple sharp diffraction peaks corresponding to the signature face-centered cubic (FCC) lattice of Prussian blue. 23,24 For CHPB NPs, the diffraction peak of Prussian blue at 2y B 17.61 of the (200) plane was observed, albeit with reduced intensity and some broadening, which is attributed to the surface coating with chitosan. Additionally, the analysis revealed that the other peaks at 2y values of 24.71 (220) and 36.41 (400) were common for both cases, suggesting that the surface coating with chitosan does not significantly alter the typical FCC crystal structure of PB.…”
Section: Characterization Of Synthesized Nanoparticlesmentioning
confidence: 99%
“…Prussian blue (PB) nanoparticles are biocompatible, cost effective and clinically approved mixed valence iron hexacyanoferrates, with the general formula Fe 4 [Fe(CN) 6 ] 3 . 23,24 They are also known to behave as an enzyme peroxidase, with applications in sensing, oxidative modulation, etc. 25,26 Moreover, these nanoparticles have broad band optical absorption in the visible and NIR window, with high molar extinction coefficients and photothermal conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a lot of nanomaterials with enzyme-mimicking properties have been discovered, including metals, metal oxides, metal sulfides, carbon materials, metal-organic frameworks (MOF) and other nanomaterials. For example, Au, [22][23][24][25] Fe 3 O 4 , [12,26,27] MoS 2 , [28] graphene quantum dots (GQDs), [29,30] Au-MOF, [31,32] Prussian blue NPs (PBNPs) [33][34][35][36] have been shown to possess enzyme-like activities. Some MOF-derived metal oxides and even singleatom nanomaterials have been reported to exhibit high enzyme-mimicking activities.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] Among them, several nanozymes have shown great potential in the detection of bacteria and viruses. [33][34][35][36]42] According to the World Health Organization, infectious diseases lead to more than 25 % of global deaths, most of which are generated by bacteria and viruses. [43] Contaminated water and food are important sources of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%